SHCal20 Southern Hemisphere Calibration, 0–55, 000 Years cal BP. Issue 4 (12th August 2020) - Hogg, Alan G; Heaton, Timothy J; Hua, Quan; Palmer, Jonathan G; Turney, Chris SM; Southon, John; Bayliss, Alex; Blackwell, Paul G; Boswijk, Gretel; Bronk Ramsey, Christopher; Pearson, Charlotte; Petchey, Fiona; et al.
ABSTRACT: Early researchers of radiocarbon levels in Southern Hemisphere tree rings identified a variable North-South hemispheric offset, necessitating construction of a separate radiocarbon calibration curve for the South. We present here SHCal20, a revised calibration curve from 0–55, 000 cal BP, based upon SHCal13 and fortified by the addition of 14 new tree-ring data sets in the 2140–0, 3520–3453, 3608–3590 and 13, 140–11, 375 cal BP time intervals. We detail the statistical approaches used for curve construction and present recommendations for the use of the Northern Hemisphere curve (IntCal20), the Southern Hemisphere curve (SHCal20) and suggest where application of an equal mixture of the curves might be more appropriate. Using our Bayesian spline with errors-in-variables methodology, and based upon a comparison of Southern Hemisphere tree-ring data compared with contemporaneous Northern Hemisphere data, we estimate the mean Southern Hemisphere offset to be 36 ± 27 14 C yrs older.